1986
DOI: 10.1007/bf00219208
|View full text |Cite
|
Sign up to set email alerts
|

A reinvestigation of the Gn-RH (gonadotrophin-releasing hormone) systems in the goldfish brain using antibodies to salmon Gn-RH

Abstract: The organization of Gn-RH systems in the brain of teleosts has been investigated previously by immunohistochemistry using antibodies against the mammalian decapeptide which differs from the teleostean factor. Here, we report the distribution of immunoreactive Gn-RH in the brain of goldfish using antibodies against synthetic teleost peptide. Immunoreactive structures are found along a column extending from the rostral olfactory bulbs to the pituitary stalk. Cell bodies are observed within the olfactory nerves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
68
1
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(81 citation statements)
references
References 57 publications
(79 reference statements)
11
68
1
1
Order By: Relevance
“…procedure. The vaiue of these results is reinforced by the fact that alternating sections of the same pituitaries were used to determine if the tGnRH cell bodies in the ven tral preoptic region project to the pituitary [24], There was an excellent correlation between the absence of tGnRH fi bers in the pituitary following the lesion and that of the TH fibers in the PD. Since the tGnRH perikarya are located at the same transverse level, although more laterally, than the CA cell bodies of the ventral preoptic region, it is not sur prising that both populations were destroyed by the same lesions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…procedure. The vaiue of these results is reinforced by the fact that alternating sections of the same pituitaries were used to determine if the tGnRH cell bodies in the ven tral preoptic region project to the pituitary [24], There was an excellent correlation between the absence of tGnRH fi bers in the pituitary following the lesion and that of the TH fibers in the PD. Since the tGnRH perikarya are located at the same transverse level, although more laterally, than the CA cell bodies of the ventral preoptic region, it is not sur prising that both populations were destroyed by the same lesions.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the pituitary receives fibers, not characterized ultrastructurally, and containing different peptides, such as corticotropin-releasing factor (CRF) or somatostatin, some of which likely originate from the pre optic region [19,30]: however, on the basis of in vivo and in vitro studies, there is no evidence for influences of cortico tropin-releasing factor or somatostatin on GTH secretion in goldfish [T. Marchant and R. Peter, unpublished results]. Cell bodies reacting to antibodies to tGnRH and projecting to the pituitary were also reported in the lateroventral pre optic region of the goldfish [24].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the organization of central GnRH systems has mainly been studied by means of immunohistochemistry using antibodies more or less specific for the endogenous decapeptides. Despite this lack of specificity, this technique has allowed the establishment of the organization of the GnRH systems in teleosts, and the presence of immunoreactive GnRH cells not only in the ventral forebrain, but also in the midbrain tegmentum (Münz et al 1981, Kah et al 1986. But specificity turned out to be a critical problem when it became clear that different forms of GnRH were produced in the brain of a single species (Yu et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the GnRH innervation of the pituitary gland (e.g. Kah et al 1986, Amano et al 1991, Rosenblum et al 1994, Yamamoto et al 1995 suggested that, in fish, sGnRH may have a more important role to play in pituitary gland function than cGnRH-II.…”
Section: Introductionmentioning
confidence: 99%